1978
DOI: 10.1111/j.1398-9995.1978.tb01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prevalence of Culturable Mesophilic Microfungi in House Dust from 100 Danish Homes

Abstract: In order to encircle possible allergen sources, fungi from house dust were cultivated and identified. Dust from vacuum cleaners was inoculated on Petri dishes containing V-8 agar with addition of penicillin and streptomycin to eliminate the bacterial flora. The number of genera identified were for the most part consistent with the genera trapped from the air. However, presumably owing to their dispersal biology it was demonstrated that members of Mucorales were much more frequently represented in the samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 10 publications
3
30
1
2
Order By: Relevance
“…The occurrence of microfungi from the beds corresponds fairly well with a former investigation of the occurrence of microfungi in Danish house-dust (Gravesen 1978). In house-dust the microfungi most frequently found was: Mircor, Penicilliitm, Alternaria, Cladosporiitrn and Aspergillus.…”
Section: Methodssupporting
confidence: 88%
“…The occurrence of microfungi from the beds corresponds fairly well with a former investigation of the occurrence of microfungi in Danish house-dust (Gravesen 1978). In house-dust the microfungi most frequently found was: Mircor, Penicilliitm, Alternaria, Cladosporiitrn and Aspergillus.…”
Section: Methodssupporting
confidence: 88%
“…(37) and discriminates against fungi that produce small amounts of spores, large spores, or spores in slime, such as Acremonium spp., Chaeto- on May 11, 2018 by guest http://aem.asm.org/ mium spp., Stachybotrys spp., Trichoderma spp., and Ulocladium spp. Besides, fungal diversity is different in outdoor air (22), in indoor air (12), and in house dust (13,53) compared with each other and with moldy building materials (14). Air sampling alone may give an incorrect picture of the fungal diversity actually present in a moldy building.…”
Section: Discussionmentioning
confidence: 99%
“…Concrete is mostly used to cast foundations, floors, and other horizontal structures and will hold soil, dirt, and dust better than vertical surfaces. These Aspergillus, Chaetomium, and Mucor species are common in dust (13) and in hypersaline water and soil (16,44). They may be introduced along with dirt and may tolerate alkaline conditions in the concrete, beginning to grow when the concrete gets wet.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling settled dust has long been proven useful in characterizing the microbial status of buildings (8). More recently, Chao et al (2) reported that the type of culturable fungi detected in settled dust from nonfloor surfaces was a significant predictor of nonspecific symptoms.…”
Section: Discussionmentioning
confidence: 99%